Performance-Based Remuneration for Civil Servants - Christoph Behrens; Pradnya Paramitha (Jurnal Studi Pemerintahan, 2011)
Within the ongoing discussion about the Governance system in Indonesia and a reform of its Public Administration according to principles of Good Governance, a new remuneration system for civil servants is regarded a strategic key issue. The article outlines dimensions of the issue and gives an insight on discourse and current reform approaches. An outlook on necessary steps ahead stresses, that Administrative Reform is not a topic for the Government only, and defines the role of different actors within a democratic Governance system.